Effectiveness of the recruitment and selection procedures of LafargeHolcim Bangladesh Limited - Shahriyar, Mahbub (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.